Quality of life in Universidad Nacional de San Cristóbal de Huamanga professors during the climacteric - Rodríguez Lizana, Maritza (2021)
Objective. To determine the quality of life in Universidad Nacional San Cristóbal de Huamanga (Peru)  professors during the climacteric.  Methods. A basic, descriptive,  observational, cross-sectional and  prospective research was conducted with a non-probabilistic and  intentional sample of 30 Universidad Nacional San Cristóbal de Huamanga professors, with prior informed  consent. The survey technique was  used for data collection and the  Menopause Rating Scale (MRS)  questionnaire, adapted to Google  forms, was used as a tool. Results. Professors during the climacteric, in a greater percentage (38.9%), considered mild symptoms in the urogenital domain, followed by somatic and psychological domain (37.5%); severe symptoms were manifested only in the somatic (7.5%) and psychological domains (5.8%). Conclusions. The MRS scale detected a greater deterioration of the  psychological and somatic domain against the urogenital, causing a  detriment in the quality of life in Universidad Nacional San Cristóbal de Huamanga professors during theclimacteric